Singkawang from Coser’s Perspective - Wasis Suprapto; Bunyamin Maftuh; Helius Sjamsuddin; Elly Malihah (STKIP Singkawang, 2020)
History records that Singkawang was an inseparable part of the conflict between ethnic groups in West Kalimantan. This article aims to examine three things, namely (1) the description of Coser's structuralist theory, (2) the strategic role of the city of Singkawang, and (3) the relevance of Singkawang City to Coser's theory. This research was studied with a qualitative descriptive. The research subject is the object of research is the city of Singkawang. Data collection techniques are carried out by literature study, interviews, and observations. The results showed that (1) the presence of conflict can play a role in restoring the social integration of members of society. Besides, the presence of conflict also plays a role in strengthening the social and emotional bonds of its followers. (2) Singkawang had a strategic role as a trading area and transit point for gold miners during the Sambas Sultanate. This condition lasted for a long time and made the people of Singkawang at that time learn to blend in with each other. In its development, the history of assimilation made the city of Singkawang finally used as one of the locations when there was an inter-ethnic conflict in West Kalimantan. (3) Coser's theory teaches that to avoid conflict there needs to be a safety value. In Singkawang City, safety value is carried out through natural assimilation through marriage, including culture. Apart from that, there is also artificial assimilation carried out by creating associations of both ethnicity and religion.